COVID-19 and menstrual-related disturbances: a Spanish retrospective observational study in formerly menstruating women - González, María; Al-Adib, Miriam; Rodríguez, Ana B.; Carrasco, Cristina (Frontiers in Global Women's Health, 2024)
Introduction Four years after the start of the pandemic, there is limited evidence on the impact of COVID-19 on the women's health regardless of their reproductive status. Objective The aim was to analyze the prevalence and associated factors of menstrual-related disturbances in formerly menstruating women following SARS-CoV-2 infection. Study design A retrospective observational study of adult women in Spain was conducted during the month of December 2021 using an online survey (N = 17,512). The present analysis includes a subpopulation of SARS-CoV-2-infected and formerly menstruating women (n = 72). The collected data included general characteristics, medical history, and specific information on COVID-19. Chi-square and Mann-Whitney U-tests were performed. Bivariate logistic regression analysis was then performed to investigate possible associations between the occurrence of menstrual-related disturbances after SARS-CoV-2 infection. Results 38.8% of participants experienced menstrual-related disturbances following COVID-19. Among these, unexpected vaginal bleeding (20.8%) was the most common event, followed by spotting (11.1%) ( Table 1). Other reported changes were in the length (shorter = 12.5%) and flow (heavier = 30.3%) of menstrual bleeding in comparison to their previous experience. Regression analysis revealed that being a perimenopausal woman [adjusted odds ratio (AOR) 4.721, CI 95%, 1.022–21.796, p = 0.047] and having a previous diagnosis of menorrhagia (AOR 5.824 CI 95%, 1.521–22.310, p = 0.010) were factors associated with the event. Conclusion These findings could help health professionals provide their patients with up-to-date scientific information to empower them to actively manage their reproductive health, especially in societies where menstrual health is still taboo.